VERTICAL AND TEMPORAL DISTRIBUTION OF MEDICALLY IMPORTANT MOSQUITO SPECIES IN AN ATLANTIC FOREST FRAGMENT OF SOUTHEASTERN BRAZIL: ECOLOGICAL INSIGHTS AND PUBLIC HEALTH IMPLICATIONS - Silva, Shayenne Olsson Freitas; De Mello, Cecilia Ferreira; Maia, Daniele; Alencar, Jeronimo (Journal of the American Mosquito Control Association, 2025)
Mosquitoes play a significant role in transmitting several major pathogens, with Haemagogus and Aedes species receiving considerable attention because of their vectorial capacity. The spatial and temporal distributions of mosquito vectors directly influence the maintenance of arbovirus cycles in specific areas. This study presents a spatial-temporal analysis of culicid entomofauna in an Atlantic Forest fragment in the state of Rio de Janeiro, Brazil. Collections were made from March 2020 to February 2024 using installed ovitraps at varying heights (ground level, 2 m, 4 m, and 6 m) in Fazenda Iguapé, located in the municipality of Silva Jardim. Mosquito communities were analyzed by comparing diversity and abundance indices of species per trap and assessing the temporal variation of culicid populations throughout the collection period. The most abundant species, Haemagogus leucocelaenus exhibited an increasing oviposition pattern with elevation. Aedes terrens showed a positive association with a height of 6 m. Aedes albopictus displayed the highest oviposition at a height of 6 m, followed by ground level and 4 m. The highest abundance of medically important mosquitoes at Fazenda Iguapé occurred in September and November 2023.